2011
DOI: 10.1038/ki.2010.335
|View full text |Cite
|
Sign up to set email alerts
|

Beyond genetics: epigenetic code in chronic kidney disease

Abstract: Epigenetics refers to a heritable change in the pattern of gene expression that is mediated by a mechanism specifically not due to alterations in the primary nucleotide sequence. Well known epigenetic mechanisms encompass DNA methylation, chromatin remodeling (histone modifications) and RNA interference. Functionally, epigenetics provides an extra layer of transcriptional control and plays a crucial role in normal physiological development, as well as in pathological conditions. Aberrant DNA methylation is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 116 publications
2
100
0
Order By: Relevance
“…End-stage renal disease (ESRD) is the partial or total loss of kidney function (Duseja et al, 2012). It is well recognized that CKD leading to ESRD is caused by complex pathogenic mechanisms that result from the interactions between multiple genes and environmental factors (Adler, 2006;Böger and Heid, 2011;Dwivedi et al, 2011). Due to the difficulty in stabilizing the disease, patients often develop various abnormalities in bone and mineral metabolism, which significantly increases morbidity and mortality (Erturk and DialGene Consortium, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…End-stage renal disease (ESRD) is the partial or total loss of kidney function (Duseja et al, 2012). It is well recognized that CKD leading to ESRD is caused by complex pathogenic mechanisms that result from the interactions between multiple genes and environmental factors (Adler, 2006;Böger and Heid, 2011;Dwivedi et al, 2011). Due to the difficulty in stabilizing the disease, patients often develop various abnormalities in bone and mineral metabolism, which significantly increases morbidity and mortality (Erturk and DialGene Consortium, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic regulations depend on DNA methylation, histone modification, RNA interference, and so on. It has been shown that epigenetic modifications are involved in various human diseases, for example, cancer, hypertension, diabetes, and atherosclerosis (8). Moreover, a recent study has revealed that hypermethylation of rat sarcoma (RAS) protein activator like-1 (RASAL1) is associated with the perpetuation of fibroblast activation and fibrogenesis in the kidney, leading to glomerular and interstitial fibrosis (9).…”
mentioning
confidence: 99%
“…Epigenetics is defined as the mechanism to induce heritable change in the pattern of gene expression without any changes in DNA sequences (8). Epigenetic regulations depend on DNA methylation, histone modification, RNA interference, and so on.…”
mentioning
confidence: 99%
“…Double-stranded RNAs also cause transcriptional silencing via methylation of homologous DNA promoter sequences (32) and/or formation of heterochromatin (33). This RNA interference is vital for the evolution of kidney disease (12), as miRNAs are critical in the preservation of glomerular balance (34).…”
Section: Epigenetics: Definition and Pathophysiologymentioning
confidence: 99%
“…Despite the increase in epigenetic research and the rising evidence of its relevance in the evolution of various complex disease traits, it is more prominent in oncology. Although the deviation into epigenetics by other subspecialties remains tentative, such research is largely experimental with few existing reports regarding the clinical implication of epigenetics in kidney disease (12). The aim of the current review was to appraise the role of epigenetics in CKD, and highlight potential future therapeutic pathways.…”
Section: Introductionmentioning
confidence: 99%